Importance of Health Policy and Systems Research for Strengthening Rehabilitation in Health Systems: A Call to Action to Accelerate Progress - Walter R. Frontera,; Wouter DeGroote,; Abdul Ghaffar, (Journal of the Pakistan Medical Association, 2023)
During the last few decades, the field of rehabilitation has experienced substantial development, growth, and acceptance. Rehabilitation addresses the impact of a health condition on a person’s everyday life by optimizing their functioning and reducing their experience of disability. Rehabilitation expands the focus of health beyond preventative and curative care to ensure people with a health condition can remain as independent as possible and participate in education, work, and meaningful life roles.1 A definition of rehabilitation for research purposes has been recently published.2 Scientific and clinical research have generated a body of knowledge that strongly supports the use of many rehabilitation interventions with positive outcomes in various populations and health conditions. We also have now a better understanding of the growing global need, demand, and recognition of rehabilitation around the world. For example, it has been estimated that 2.41 billion people in the world could benefit from rehabilitation services. This means that at least one in every three persons in the world needs rehabilitation at some point during the course of their disease or injury.3 This figure has most likely increased because of the COVID-19 pandemic. The need for rehabilitation increased by 63% between 1990 and 2017 because of the aging population, the increasing prevalence of noncommunicable health conditions, and the shifting epidemiological profile in most countries.3 Finally, according to the 2022 global report on health equity for persons with disabilities, approximately 1.3 billion people or 16% of the world’s population has moderate to severe levels of disability associated with the underlying health conditions and impairments.4 Now more than ever before, it is crucial that rehabilitation is available and accessible to populations globally according to their needs. The important contribution of rehabilitation to the functioning, including social and occupational participation and well-being of populations worldwide, can no longer be denied or delayed. Rehabilitation is critical for the attainment of the United Nations Sustainable Development Goal 3, Ensure healthy lives and promote well-being for all at all ages.5 Notwithstanding the foregoing arguments, there continues to be a high unmet need for rehabilitation globally, with some low- and middle-income countries reporting unmet needs up to 50% of those who could benefit from rehabilitation. Rehabilitation services are not accessible to many people around the world.6 Many of those in need do not have access because of the failure, at least partially, to effectively plan for rehabilitation services. Many nations and health systems have not implemented policy measures that recognize rehabilitation as an essential component of universal health coverage7,8 Health policy, planning, and decision making for rehabilitation often require more local evidence to adequately plan, finance, implement,and monitor quality rehabilitation services including infrastructure and workforce to make services accessible to those in need.9